HUBUNGAN KADAR NITRIT OKSIDA (NO) DALAM DARAH TERHADAP RESIKO KEJADIAN DIABETES MELLITUS TIPE 2 DENGAN HIPERTENSI DI RSUP NTB - I Gusti Ayu Nyoman Danuyanti; Erna Kristinawati; Ersandhi Resnhaleksmana (Jurnal Kesehatan Prima, 2014)
Abstract: Diabetes Mellitus (DM) is a group of metabolic diseases with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. Pathophysiology of type 2 diabetes mellitus are very complex with involving a variety of factors, including nutrition, obesity, sedentary lifestyle, and lack of physical activity, and genetik. The prolonged  of condition hyperglycemia causes endothelial cell dysfunction resulting in decreased production of various compounds that are antithrombotic and vasodilating include nitric oxide ( NO). The purpose of this study was to determine the relationship between levels of nitric oxide (NO) in the blood against the risk of incident type 2 diabetes mellitus with hypertension at the RSUP NTB. This study uses a case-control design, with a sample size of 30 people with type 2 diabetes with hypertension as the case group and 30 patients without hypertension, diabetes mellitus type as the control group. The total sample is 60 people. Dependent variable in this study is the levels of NO in the blood while the independent variables of type 2 DM patients with hypertension. Determination of levels of nitric oxide (NO) in the blood using spectrophotometric methods. Correlation test is used to determine the relationship between levels of nitric oxide (NO) in blood with the blood pressure while Chi-square test used to determine the relationship of NO levels on the risk of incident type 2 diabetes with hypertension. The results showed average mean levels of NO in patients with type 2 diabetes with hypertension was lower than 0.54 μM with type 2 DM patients without hypertension is 1.32 μM. The results of correlation test levels of NO in the blood and blood pressure showed p-value = 0.000 (<α 0.05) and there is a strong relationship with a correlation coefficient value of 0.749 for systolic blood pressure and 0.694 for diastolic. Analysis of the relationship of NO levels in the blood against the risk of incident type 2 diabetes with hypertension show the value of p = 0.000. The overall from the can be concluded There is a relationship between the amount of nitric oxide (NO) in the blood against the risk of incident type 2 diabetes mellitus with hypertension in the RSUP NTB.